PENERAPAN KONSEP GREEN HOSPITALITY PADA HOMESTAY DI DESA WISATA PANJI, KABUPATEN BULELENG - I Kadek Teddi Anggastia; I Gede Putra Nugraha; Ni Made Ary Widiastini (Universitas Pendidikan Ganesha, 2026)
This study aims to explain the implementation of green hospitality in homestays in Panji Tourism Village and to identify the barriers to its implementation using a descriptive qualitative method. Data were collected through observation, interviews, and documentation. Interviews were conducted with homestay owners and the head of the tourism awareness group (Pokdarwis) of Panji Tourism Village. The results show that environmentally friendly practices—such as waste segregation, plastic reduction, the use of energy-efficient lighting, natural ventilation, utilization of local food ingredients, and environmentally based tourism activities—have been implemented, but not optimally. This is due to the absence of standard operating procedures (SOPs), limited education for guests and managers, and constraints in facilities, technology, and funding. Nevertheless, the implementation of green hospitality has generated positive environmental, social, and economic impacts for the local community and has enhanced the attractiveness of Panji Village as a sustainable tourism destination. Panji Village has strong potential to further develop sustainable tourism through the green hospitality concept by strengthening education, village policies, and green homestay standards. Therefore, the findings of this study can serve as a reference for homestay managers, village governments, and stakeholders in the development of sustainable tourism in tourism villages.